Metal-free radical perfluoroalkylation of (hetero)arenes. Issue 9 (22nd December 2014) - Zhong, Sabilla; Hafner, Andreas; Hussal, Christoph; Nieger, Martin; Bräse, Stefan
Abstract : We report a metal-free radical perfluoroalkylation method which uses inexpensive and commercially available perfluorocarboxylic anhydrides as an easy to use source of perfluoroalkyl radicals. Abstract : We report a metal-free radical perfluoroalkylation method which uses inexpensive and commercially available perfluorocarboxylic anhydrides as an easy to use source of perfluoroalkyl radicals. This approach allows the perfluoroalkylation of different arenes, such as benzene derivatives, furans, thiophenes, and pyrroles, including highly functionalized compounds.